Fiscal Correction Analysis Of Profit And Loss Reports In Determining Corporate Income Tax At CV Karya Bhakti Sentosa - SUPIT, Sharone Sherina Benaya; LAMBE, Robert Y; WEKU, Priscilia (Journal of Governance, Taxation and Auditing, 2022)
CV Karya Bhakti Sentosa is a company engaged in the procurement and service provider industry. As a company that is obligated to pay taxes, CV Karya Bhakti Sentosa prepares commercial financial reports as the basis for calculating taxable profits and does not make fiscal corrections in accordance with the Tax Law. Fiscal corrections are corrections made due to differences in the treatment of income and expenses that differ between accounting standards and applicable tax regulations. The purpose of this study is to make and analyze fiscal corrections on income statements in determining corporate income tax at CV Karya Bhakti Sentosa. The research method used in this study is descriptive qualitative method, with data collection methods carried out by interviews and documentation. The results of this study are the company's fiscal profit of Rp. 807,100,774.00, an increase of Rp. 3,404,975.00 from the company's commercial profit which causes the company to have a difference in the payable income tax that the company has deposited in the amount of Rp. 619,954.00 underpaid.